MODEL KEBIJAKAN POLITIK PEMERINTAH LOKAL DALAM PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (Studi Pada Lembaga Legislatif Kabupaten Grobogan) - Tri Lestari Hadiati; Agus Siswanto (Universitas 17 Agustus 1945, 2023)
The political policy of the local government in establishing the Regional Revenue and Expenditure Budget (APBD), is an Annual Financial Plan (RKT) prepared by the local regional government and jointly approved by the Regional Head (KDH) and the Regional People's Representative Council (DPRD). There are certain obstacles such as the emergence of executive dominance or legislative domination in designing, discussing and approving the APBD. The purpose of this study is to analyze the political policy model of the local government (Grobogan Regency) in determining the APBD. This study uses a qualitative method whose analysis is descriptive. Researchers use naturalistic and normative juridical approaches. The data used are primary and secondary data. Data collection techniques using interviews, observation and documentation. Data analysis techniques go through four stages, namely gathering information, data reduction, data presentation, and drawing conclusions. The results of this study conclude the political policy model of executive domination that occurred in Grobogan Regency. Facts on the ground show that the political policies implemented by the Grobogan Regency DPRD have the authority to approve the RAPBD determination, as well as the authority to reject the proposed RAPBD through the factions in the DPRD. However, this rejection never occurred during the research period (2021-2022). Even if this can be done when the DPRD has valid data regarding irregularities committed by the Regional Government. This diametrical position and role relationship is because there are legal consequences if the RAPBD is rejected by the DPRD. The legal consequence is that the implementation of government activities in the institution cannot be carried out properly and it will also have fatal consequences for slowed development in its territory. However, in the end, the DPRD, through a plenary meeting, even though it was difficult, had to give approval for the determination of the APBD, which paid little attention to benefits for the community.